2003
DOI: 10.1016/j.mod.2003.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The Drm–Bowl–Lin relief-of-repression hierarchy controls fore- and hindgut patterning and morphogenesis

Abstract: The elucidation of pathways linking patterning to morphogenesis is a problem of great interest. We show here that, in addition to their roles in patterning and morphogenesis of the hindgut, the Drosophila genes drumstick (drm) and bowl are required in the foregut for spatially localized gene expression and the morphogenetic processes that form the proventriculus. drm and bowl belong to a family of genes encoding C(2)H(2) zinc finger proteins; the other two members of this family are odd-skipped (odd) and sob. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 33 publications
1
47
0
Order By: Relevance
“…First, we investigated the regulation of Bowl accumulation in the gut. Genetically, bowl is required both in the foregut, where it distinguishes proventriculus from anterior gut, and in hindgut, where it distinguishes small from large intestine (Iwaki et al 2001;Johansen et al 2003). Indeed, we found that Bowl protein accumulated in two narrow domains in the gut: the primordia for the proventriculus (Fig.…”
Section: Drm and Lines Regulate Bowl Protein Accumulation And Consequmentioning
confidence: 74%
See 3 more Smart Citations
“…First, we investigated the regulation of Bowl accumulation in the gut. Genetically, bowl is required both in the foregut, where it distinguishes proventriculus from anterior gut, and in hindgut, where it distinguishes small from large intestine (Iwaki et al 2001;Johansen et al 2003). Indeed, we found that Bowl protein accumulated in two narrow domains in the gut: the primordia for the proventriculus (Fig.…”
Section: Drm and Lines Regulate Bowl Protein Accumulation And Consequmentioning
confidence: 74%
“…Similar genetic interactions between drm and lines and between lines and bowl distinguish small and large intestine in the developing hindgut, and proventriculus and foregut proper in the developing foregut (Green et al 2002;Johansen et al 2003). Bar, 10 µm.…”
Section: (J) Ectopic Drm(c56g) (K)mentioning
confidence: 98%
See 2 more Smart Citations
“…for Drosophila hindgut development (14)) as a novel gene product promoting the progression of this malignancy (15). However, the mechanism by which ZKSCAN3 augmented colorectal tumorigenicity and progression was not addressed.…”
mentioning
confidence: 99%